Implementasi Model Pembelajaran Daring pada Masa Pandemi di SDIT Darul Ulum - Virgianti, Dita; Dewi, Indria Kusuma; Heni, Nur; Nabila, Putri (Lembaga Yasin AlSys, 2022)
The purpose of this study, namely to find out how to implement the online learning model, to find out what are the inhibiting factors in the implementation of online learning, and to find out the supporting factors in the online learning process during the pandemic. Parents' Perception of Online Learning During a Pandemic. This study uses qualitative research with descriptive analysis techniques. The results show that the implementation of the online learning model in elementary schools is by utilizing several kinds of applications, the use of one-sheet lesson plans and evaluation of written worksheets that can be taken and collected directly to the school supported by facilities provided by the school in the form of wifi for teachers at school. and free internet quota for students. However, there are still obstacles in the implementation of online learning, namely, the lack of effectiveness and time efficiency, the lack of student enthusiasm and the lack of understanding of the material.